PENERAPAN HEALING ENVIRONMENT PADA PERANCANGAN SEKOLAH DASAR LUAR BIASA BAGIAN TUNALARAS - Bihastuti, Endhita Januar; Nirawati, Maya Andria; Mustaqimah, Ummul (ARSITEKTURA, 2017)
Children  with emotional and behavioral disorders are one of  kind children with special education need.  Education as a basic right of every child in Indonesia, especially children with emotional and behaviour disorder, has not been fully realized, this is due to the lack of awareness of parents and teachers. The earlier the children with emotional and behaviour disorders are detected, the higher the expectation to recovery is, so special elementary school for emotional and behaviour disorder facilities are essential. For designing a building that maximizes space program and environmental atmosphere available with the type of needs and program activities that take place, the healing environment is chosen as a design solution at the planned school. Healing environment is related to the creation of an environment that affects health by influencing action and interaction by applying the sensory, natural, and psychological aspects. Aspects of the healing environment will be applied to the spatial, site, form and mass arrangement, and landscape.